Pengaruh kualitas konten promosi produk skincare terhadap customer engagement (Studi survei pada followers akun instagram @beliacosmetic) - Yuliana Lestari; Herma Retno Prabayanti (Universitas Negeri Surabaya, 2025)
This study aims to analyze the effect of the quality of promotional content of skincare products on customer engagement on Instagram @beliacosmetic. The research uses an explanatory quantitative method with 100 respondents selected using purposive sampling technique. The focus of the research is two main indicators, namely efficiency and quality of promotional content, during the period January to March 2024. Data was obtained through a questionnaire measured using a Likert scale with reverse values for positive and negative questions. The results show that content quality has a significant influence on audience cognitive, affective, and behavioral engagement, with the behavioral engagement indicator showing the highest average. Based on the results of regression analysis, efficiency and content quality simultaneously contribute greatly to customer engagement.